2016
DOI: 10.3390/f7070129
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variability of Wildland Fuels in US Northern Rocky Mountain Forests

Abstract: Abstract:Fire regimes are ultimately controlled by wildland fuel dynamics over space and time; spatial distributions of fuel influence the size, spread, and intensity of individual fires, while the temporal distribution of fuel deposition influences fire's frequency and controls fire size. These "shifting fuel mosaics" are both a cause and a consequence of fire regimes. This paper synthesizes results from two major fuel dynamics studies that described the spatial and temporal variability of canopy and surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 55 publications
(81 reference statements)
1
8
0
Order By: Relevance
“…Where explanatory variables are not available, mean and standard deviation values of DWD by species and ecozone provide a much needed starting point to calibrate models. The databases analysed in this study revealed a wide range in DWD fuel loads, as also shown in other studies (Keane 2016). As previously mentioned, species and climatic gradients strongly influence DWD production (Bernier et al 2007), accumulation (Allard and Park 2013) and decomposition (Harmon et al 2000).…”
Section: Discussionsupporting
confidence: 85%
“…Where explanatory variables are not available, mean and standard deviation values of DWD by species and ecozone provide a much needed starting point to calibrate models. The databases analysed in this study revealed a wide range in DWD fuel loads, as also shown in other studies (Keane 2016). As previously mentioned, species and climatic gradients strongly influence DWD production (Bernier et al 2007), accumulation (Allard and Park 2013) and decomposition (Harmon et al 2000).…”
Section: Discussionsupporting
confidence: 85%
“…There is also an assumption that the site attributes consistently co-vary-i.e., that bulk density and crown base height are at consistent ratios for a particular vegetation class. This assumption may not be always valid as natural systems often have gradients of change [94] and high levels of independent variation occur in space and time in both species composition and fuel attributes [25,27,38,95]. The importance of considering this variation is particularly evident at the interface between wildlands and urban environments where vegetation is heavily modified (resulting in novel fuel configurations that are not well represented by existing classifications) and there are high concentrations of values at risk (so there are potentially greater consequences for errors) [96].…”
Section: Summarizing Fuel To Develop Mapsmentioning
confidence: 99%
“…There are a number of sources of error that may contribute to poor results. These include (1) inappropriate fuel sampling methods and designs; (2) improper classifications; (3) errors in the application of methods; (4) improper geo-registration; and (5) scale incompatibilities (both between fuel attributes at a site and between sampling scale and mapping scale) [3,95]. The level of error in using classes can be high: a review of the LANDFIRE fuel mapping products found that correlation between mapped units and fuel properties was relatively low (ranging between 5% and 85% correct, regardless of mapping approach) due to scale and resolution mismatches and the possible insensitivity of the attributes used [121].…”
Section: Creating Maps Of Fuelmentioning
confidence: 99%
“…Under this context, unraveling the determinants that make forests more vulnerable to high-intensity crown fires has emerged as a research and technical issue of utmost importance (Alvarez et al, 2013;Sande Silva et al, 2010). Among factors influencing fire behavior -weather, topography, and vegetation -a major effort must be done to understand the role of spatial and temporal variations of fuel characteristics (Keane, 2016;Simeoni et al, 2011). Indeed, the distribution and characteristics of plant biomass are the factors that mostly govern the combustion processes (Weise and Wright, 2014) and fire hazard (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, multiple overstory-understory combinations of heterogeneous landscapes may result in even greater variability of forest fuel characteristics and fire behavior at the stand level (Baeza et al, 2002;Curt et al, 2011;Fernandes et al, 2008;Santana et al, 2011). Besides, the effects of forest dynamics together with climate and land-use changes may influence the rate of variation of fuel characteristics in vegetation strata depending on species composition or environmental conditions (Keane, 2016;Sánchez-Pinillos et al, 2019).…”
Section: Introductionmentioning
confidence: 99%